2016
DOI: 10.1021/acs.jpcc.6b03891
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Vibrations Induced Potential Diradical Character in Hexazapentacene

Abstract: While the photoelectrochemical behavior of azapentacene has been investigated successfully, insight into the dynamic electronic properties of azapentacene triggered by different energy pulses is very scarce. The present work reports a fascinating phenomenon about potential diradical character governed by structural vibrations in hexazapentacene. In complete contrast to the static equilibrium configuration of hexazapentacene without diradical character, due to the vibration-based structural perturbation, DFT ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…18 They also predicted a transition in electronic structure from discrete molecular orbitals to band picture occurs for octacene onwards. 18 Such interconversion in the electronic structure in polyacenes has consequences on its ground state molecular properties such as optical 19 , magnetic 20 , vibrational, 21 and other spectroscopic properties 22 . Here such linear polyacenes are adopted as the spacers in coupling the conformationally restricted nitroxy-diradicals.…”
Section: Introductionmentioning
confidence: 99%
“…18 They also predicted a transition in electronic structure from discrete molecular orbitals to band picture occurs for octacene onwards. 18 Such interconversion in the electronic structure in polyacenes has consequences on its ground state molecular properties such as optical 19 , magnetic 20 , vibrational, 21 and other spectroscopic properties 22 . Here such linear polyacenes are adopted as the spacers in coupling the conformationally restricted nitroxy-diradicals.…”
Section: Introductionmentioning
confidence: 99%
“…Such interconversion in the electronic structure of polyacenes i.e. from closed-shell singlet to open-shell singlet has consequences on its ground state molecular properties such as optical [28], magnetic [27], vibrational, [29] and other spectroscopic properties [30]. Here such linear polyacenes are adopted as the spacers in coupling the conformationally restricted nitroxy-diradicals.…”
mentioning
confidence: 99%
“…Undoubtedly, these findings have fully confirmed that molecular vibration could lead to the expected or unexpected effects in charge transfer or other electronic dynamics applications. Furthermore, our group also theoretically demonstrated that molecular inherent vibrations could induce intriguing dynamic diradical character in pentacene, hexazapentacene, and perfluoropentacene . Besides, the β‐turn motifs have been found to be more flexible than the β‐sheet motifs in controlling the efficiency of proton transfer between reactive centers and should also play an intriguing role in assisting charge transfers.…”
Section: Introductionmentioning
confidence: 91%
“…To examine the gradual variations of the relaying properties in vibrational progress of a specific vibrational mode, the dynamic process of a specific vibrational mode is represented by a given number of consecutive snapshots, and hence described by R = R 0 ± n Δ R , where Δ R is an increment of coordinate change and n = 1–10, while + n Δ R and – n Δ R denote the positive and negative shifts, respectively. This method has been proved to be suitable to discussing the vibrational effects in our previous work . Further, the corresponding energies of neutral and anionic distorted and static configurations, spin density distributions, and LUMO and SOMO energies were obtained.…”
Section: Calculational Detailsmentioning
confidence: 99%